2019
DOI: 10.1242/bio.044867
|View full text |Cite
|
Sign up to set email alerts
|

Failure to identify modifiers of NEBULIN related nemaline myopathy in two pre-clinical models of the disease

Abstract: Nemaline myopathy is a rare neuromuscular disorder that affects 1 in 50,000 live births, with prevalence as high as 1 in 20,000 in certain populations. 13 genes have been linked to nemaline myopathy (NM), all of which are associated with the thin filament of the muscle sarcomere. Of the 13 associated genes, mutations in NEBULIN (NEB) accounts for up to 50% of all cases. Currently, the disease is incompletely understood and there are no available therapeutics for patients. To address this urgent need for effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Locomotion is a complex trait that may be difficult to modify, especially in the double mutant fish which are completely paralyzed. We have observed mixed results with this outcome measure in other zebrafish myopathy models, where we have successfully identified chemicals that rescue the swimming defect in mtm1 mutant zebrafish (Sabha et al, 2016), meanwhile we found no positive hits in neb deficient zebrafish which show complete paralysis (Qiu et al, 2019). As discussed below, we believe development of new models that do not completely lack RyR1 expression and that more closely mirror human mutations will overcome this limitation in the future.…”
Section: Discussionmentioning
confidence: 88%
“…Locomotion is a complex trait that may be difficult to modify, especially in the double mutant fish which are completely paralyzed. We have observed mixed results with this outcome measure in other zebrafish myopathy models, where we have successfully identified chemicals that rescue the swimming defect in mtm1 mutant zebrafish (Sabha et al, 2016), meanwhile we found no positive hits in neb deficient zebrafish which show complete paralysis (Qiu et al, 2019). As discussed below, we believe development of new models that do not completely lack RyR1 expression and that more closely mirror human mutations will overcome this limitation in the future.…”
Section: Discussionmentioning
confidence: 88%